2017
DOI: 10.3390/met7010027
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Austenitizing Conditions on the Microstructure of AISI M42 High-Speed Steel

Abstract: Abstract:The influences of austenitizing conditions on the microstructure of AISI M42 high-speed steel were investigated through thermodynamic calculation, microstructural analysis, and in-situ observation by a confocal scanning laser microscope (CSLM). Results show that the network morphology of carbides could not dissolve completely and distribute equably in the case of the austenitizing temperature is 1373 K. When the austenitizing temperature reaches 1473 K, the excessive increase in temperature leads to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 24 publications
0
18
0
Order By: Relevance
“…The as-cast structure of AISI M42 HSS can be divided into two types of constructions: a dendritic matrix of ferrite with small carbides and a ledeburite of carbides and ferrite. A previous study 19 demonstrated that the smaller carbides were mostly V-rich MC or M(C,N), while the large primary carbides were Mo-rich M 2 C. In conventional M42 steel, the morphology of M 2 C carbides presents a lamellar shape with dimensions of 5 to 20 μm in length and 1 to 2 μm in width (Fig. 3(a) ).…”
Section: Resultsmentioning
confidence: 87%
“…The as-cast structure of AISI M42 HSS can be divided into two types of constructions: a dendritic matrix of ferrite with small carbides and a ledeburite of carbides and ferrite. A previous study 19 demonstrated that the smaller carbides were mostly V-rich MC or M(C,N), while the large primary carbides were Mo-rich M 2 C. In conventional M42 steel, the morphology of M 2 C carbides presents a lamellar shape with dimensions of 5 to 20 μm in length and 1 to 2 μm in width (Fig. 3(a) ).…”
Section: Resultsmentioning
confidence: 87%
“…The typical microstructure in the as-cast alloy consists of dendrites surrounded by coarse M 2 C-type eutectic carbides with a networked structure. These coarse primary carbides undergo decomposition, dissolution, transformation, and precipitation during hot deformation, and transform into a more stable form that can be expressed as M 2 C + matrix→M 6 C + MC [6,7,8,9]. Nogueira et al [10] reported that undecomposed reticular carbides could provide routes for crack propagation and make cracks deeper.…”
Section: Introductionmentioning
confidence: 99%
“…Austenitization temperature plays an important role in these steels since it influences several microstructural features e.g. ; prior austenite grain size, morphology of martensitic lath structure, volume fraction of primary carbides (carbides retained after austenitizing treatment are called primary carbides whereas carbides formed during tempering are called secondary carbides), amount of alloying elements dissolved in the austenite and the amount of retained austenite [4][5][6][7][8]. Higher the austenitizing temperature, a greater amount of alloying elements is expected to be dissolved in the austenite [9]; therefore full potential of these alloying elements can be exploited during subsequent quenching-tempering process in which secondary hardening precipitates form.…”
Section: Introductionmentioning
confidence: 99%
“…Higher the austenitizing temperature, a greater amount of alloying elements is expected to be dissolved in the austenite [9]; therefore full potential of these alloying elements can be exploited during subsequent quenching-tempering process in which secondary hardening precipitates form. However higher austenitizing temperatures also results in increasing the prior austenite grain size [7,[10][11][12][13][14]. At the same time, lower the austenitization temperature, finer is the prior austenite grain size, and greater is the fraction of undissolved primary carbides in the austenite which decreases the secondary hardening effect and also reduces the fracture toughness of the steel [4,15,16].…”
Section: Introductionmentioning
confidence: 99%